The Fountainhead of African Identity-crisis: A Post-colonial Analysis of Chinua Achebe’s Things Fall Apart - Malesela Edward Montle (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
The African society in the present era is vexed by horrendous altitudes of identity-crises. This marks the unyielding discriminatory and stereotypical outlooks that persist in marginalising African identities despite the various efforts that emerged to rehabilitate them in the post-colonial arena. This paper aimed to deconstruct the base of identity-crisis in the African context to establish the mainspring behind the crisis from a literary standpoint. In this regard, a literary text that mirrors the colonial setting of Africa has been chosen to be utilised as a case in point. Chinua Achebe’s Things Fall Apart is a germane text for the paper and has been employed as a lens to probe the focal theme of the study. Furthermore, this study has relied on a qualitative research method to deconstruct the fountainhead of the African Identity-crisis. The data collected from the literary text has been textually analysed. The study, inter alia, finds that the contact between Africa and the West during the colonial period engendered identity-crisis that is still a problem in Africa despite the continent being no longer under colonial rule. This crisis is perpetuated by colonial remnants such as Western cultures and perceptions that are still predominant in Africa.